Effects of Butterfly Pea (Clitoria ternatea) Powder and Cocoa Butter Replacer on the Physicochemical and Sensory Properties of White Chocolate (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
This study investigated the effects of butterfly pea flower powder (BPP) and cocoa butter replacer (CBR) on the physicochemical and sensory properties of white chocolate, addressing the increasing demand for functional and sustainable food products. Six formulations were created, varying BPP (3% and 5%) and CBR (0%, 10%, and 36.8%). Comprehensive analyses included colour metrics, moisture content, pH, water activity, texture, melting behaviour, fatty acid composition, and sensory evaluations by semi-trained panellists. Results indicated that BPP significantly enhanced blue hues due to anthocyanins but also increased moisture content and water activity due to its hygroscopic properties. Conversely, higher CBR levels lightened the colour, reduced yellow tones by replacing carotenoid-rich cocoa butter, and reduced moisture and water activity, attributed to its hydrophobic nature. The pH ranged from 6.78 to 6.89, with slight increases at higher CBR levels. Texture analysis revealed that increased CBR levels softened the chocolate due to the absence of cocoa butter's crystalline structure. Melting profiles exhibited dual phases in CBR-containing samples, which were linked to triglyceride diversity. In contrast, higher BPP levels disrupted fat crystallization, thereby impacting thermal stability. Sensory evaluations showed that formulations without CBR were more acceptable due to their superior texture and flavour, whereas higher BPP levels, along with added functional benefits, negatively influenced sensory scores due to bitterness and insolubility. The study concluded that while BPP and CBR present innovative opportunities, careful balancing is essential to maintain quality. One improvement is to create dairy-free white chocolate with coconut milk powder as a substitute for milk powder. This offers a creamy texture, mild sweetness, and nutritional benefits while meeting demand for allergen-free, vegan, and sustainable products.
Keywords: Cocoa butter; Cocoa butter replacer; Butterfly pea powder; Physicochemical properties; Sensory properties